Platelet Function and the Bleeding Time in Progressive Renal Failure - Gordge, M P; Faint, R W; Rylance, P B; Neild, G H (Thrombosis and Haemostasis, 1988)
Bleeding time and platelet function tests were performed on 31 patients with progressive chronic renal failure (CRF) due to non-immunological (urological) causes, and compared with 22 healthy controls. Patients were classified as mild (plasma creatinine <300 μmol/l), moderate (300-600 μmol/l) or severe renal failure (>600 μmol/l). Bleeding time was rarely prolonged in mild and moderate CRF and mean bleeding time significantly elevated only in severe CRF (p <0.005). Haematocrit was the only index which correlated with bleeding time (r = -0.40). Platelet counts, collagen stimulated thromboxane generation, and platelet aggregation responses to ADP, collagen and ristocetin were all either normal or increased in all three CRF groups, but thromboxane production in clotting blood was reduced. Plasma fibrinogen, C reactive protein and von Willebrand factor (vWF) were elevated in proportion to CRF. We found no evidence that defects in platelet aggregation or platelet interaction with vWF prolong the bleeding time in patients with progressive CRF.
Keywords: Platelets; Bleeding time; Renal failure